XUV double‐pulses with femtosecond to 650 ps separation from a multilayer‐mirror‐based split‐and‐delay unit at FLASH. (3rd August 2018) - Sauppe, Mario; Rompotis, Dimitrios; Erk, Benjamin; Bari, Sadia; Bischoff, Tobias; Boll, Rebecca; Bomme, Cédric; Bostedt, Christoph; Dörner, Simon; Düsterer, Stefan; Feigl, Torsten; Flückiger, Leonie; et al.
Abstract : In order to probe the complex dynamics of light–matter interaction on all relevant time scales, a multilayer‐mirror‐based long‐range split‐and‐delay unit was installed as a part of the CAMP end‐station at the FLASH free‐electron laser in Hamburg. Abstract : Extreme ultraviolet (XUV) and X‐ray free‐electron lasers enable new scientific opportunities. Their ultra‐intense coherent femtosecond pulses give unprecedented access to the structure of undepositable nanoscale objects and to transient states of highly excited matter. In order to probe the ultrafast complex light‐induced dynamics on the relevant time scales, the multi‐purpose end‐station CAMP at the free‐electron laser FLASH has been complemented by the novel multilayer‐mirror‐based split‐and‐delay unit DESC (DElay Stage for CAMP) for time‐resolved experiments. XUV double‐pulses with delays adjustable from zero femtoseconds up to 650 picoseconds are generated by reflecting under near‐normal incidence, exceeding the time range accessible with existing XUV split‐and‐delay units. Procedures to establish temporal and spatial overlap of the two pulses in CAMP are presented, with emphasis on the optimization of the spatial overlap at long time‐delays via time‐dependent features, for example in ion spectra of atomic clusters.